A nomogram based on the red cell distribution width to lymphocyte ratio as a prognostic tool for non-muscle-invasive bladder cancer: a retrospective study - Song, Feifan; Su, Shiqiang; Zhang, Xueqiao; Cao, Yunpeng; Cui, Xiongjie; Zhang, Lili; Li, Chao; Li, Shen; Tian, Shuo; Liu, Lizhe (Frontiers in Oncology, 2026)
BackgroundThis study investigated the prognostic value of the preoperative red cell distribution width to lymphocyte ratio (RLR) for recurrence-free survival (RFS) and overall survival (OS) in patients with non-muscle-invasive bladder cancer (NMIBC) undergoing transurethral resection of bladder tumor (TURBT).MethodsA retrospective analysis was performed on data from 239 patients who received TURBT. The optimal RLR cutoff was determined using time-dependent receiver operating characteristic (ROC) curve analysis. Survival outcomes were assessed using Kaplan-Meier curves and univariate/multivariate Cox regression. An RFS prognostic nomogram incorporating independent factors was developed and evaluated via the concordance index (C-index), calibration plots, time-dependent ROC, and decision curve analysis (DCA). Subgroup analyses assessed the consistency of the RLR-RFS association.Results: Elevated preoperative RLR was an independent prognostic factor for worse RFS and OS. Moreover, compared to the platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR), RLR demonstrated relatively higher predictive performance for 1-year and 3-year RFS. The novel nomogram incorporating the RLR parameter demonstrated improved predictive accuracy and a trend toward greater net clinical benefit compared to the conventional model based solely on the EORTC recurrence risk classification. Subgroup analysis indicated a stronger relationship between high RLR and poor RFS in patients with pTaN0M0 compared to those with pT1N0M0.ConclusionPreoperative RLR represents a potential independent prognostic indicator for tumor recurrence in NMIBC patients following TURBT. The RLR-based nomogram may improve recurrence risk prediction in this population.